Trade Openness and Growth in Developing Countries: An Analysis of the Relationship after Comparing Trade Indicators - Fenira, Mohamed (Asian Economic and Financial Review, 2015)
The paper demonstrates that trade policy liberalization have weakly contributed in improving economic growth in 82 developing countries two years after the Uruguay round and until 2012. The assertion is preceded by a trade indexes comparative analysis in order to prove that the (X+M/GDP) trade ratio, used as variable of interest in our model, is less exposed to methodological shortcomings faced by three trade openness indexes, commonly used in empirical literature, namely the Sachs and Warner (1995), the Dollar and Kraay (2002) and the Wacziarg and Welch (2003) indexes. Finally, the paper attributes liberal policies measures in developing countries to the presence of a strong positive association between the “official development assistance and official aid” variable and (X+M/GDP) ratio.